A bilingual–monolingual comparison of young children's vocabulary size: Evidence from comprehension and production. (28th January 2013) - DE HOUWER, ANNICK; BORNSTEIN, MARC H.; PUTNICK, DIANE L.
ABSTRACT It is often assumed that young bilinguals are lexically delayed in comparison to monolinguals. A comprehensive comparison of comprehension and production vocabulary in 31 firstborn bilingual and 30 matched monolingual children fails to find empirical foundation for this assumption. Several raters completed Dutch and French adaptations of the MacArthur Communicative Development Inventories for children aged 13 and 20 months. At 13 months, bilinguals understood more words than did monolinguals; at 20 months, monolinguals knew more Dutch words than did bilinguals (combining comprehension and production). There were no group differences for word production or for Dutch word comprehension. Both groups understood and produced the same number of lexicalized meanings; ratios of word comprehension to word production did not differ; interindividual variation was similar. This study underscores the importance of conducting bilingual–monolingual comparisons with matched groups and suggests that if individual bilingual children appear to be slow in early vocabulary development, reasons other than their bilingualism should be investigated.